The Washback effect of the Iranian universities entrance exam: teachers’ insights - Hadi Salehi,; Melor Md Yunus, (Penerbit UKM, 2012)
The Entrance Exam of the Universities (EEU) in Iran is a multiple-choice high-stakes test which clearly affects its stakeholders. This effect, generally known as washback, can be considered negative or positive depending on the test and its intended use. The EEU is designed to screen the high school graduates for admission into higher education. This study aimed to investigate the washback effect of this high-stakes test on the Iranian high school English teachers. To achieve the aim of the study, a validated survey questionnaire was administered to stratified random sample of 132 high school English teachers who were teaching in the five main educational districts in the city of Isfahan, Iran. The data analysis revealed that the EEU negatively and implicitly influences English teachers to teach to the content and format of the test. Additionally, little attention was given to three language skills of speaking, writing, and listening in the classroom as these skills are not tested in the EEU.